Development of Standard Thai Dessert Recipes from Sago Palm Flour from Phatthalung Province - Punfujinda, Chaiyasit; Salee, Marin; Songpranam, Pongsak; Tula, Poomipong; Chumkaew, Krittin (Dusit Thani College Journal, 2022)
The research study aimed to develop standard Thai dessert recipes made from sago palm flour by applying sago palm flour from Phatthalung Province and developing ingredients for seven Thai dessert recipes. The seven desserts were derived from the consumer survey in developing Thai dessert recipes from sago palm flour. Thirty participants including instructors and students in Food and Nutrition major, were asked to complete a 5-point-rating scale questionnaire to evaluate the seven recipes based on the following seven criteria: serving size, characteristics of desserts, color, odor, taste, texture and overall satisfaction. The results revealed the 7 recipes of Thai desserts from sago palm flour had the highest level of overall satisfaction. Then, the standard recipes were carried out and publicized to customers who buy sago palm flour and individuals who might be interested in it. Lastly, the satisfaction levels of the users of the Thai dessert standard recipes from sago palm flour were evaluated. The results showed all eight aspects received the highest levels of overall satisfaction. In addition, the questionnaire respondents reported that they benefited from the recipes the most, accounting for 66%,